MATLAB-based musical instrument changer - Tang, Fabian Yao Wen (2016)
MATLAB is a computer-based platform that enables analysis and development for many scientific and engineering solutions. Its versatility and application in many technical fields allows for the exploration of many problems and ideas within a desktop environment. In light of MATLAB’s Signal Processing capabilities, this project seeks to explore the manipulation of the properties of musical audio recordings so that, when played back, the audio waveform resembles an identical piece of music performed on a different musical instrument.